IoT-Enabled Solar-Powered Pest Control for Rice Agriculture: Monitoring and Efficiency of Light-Based Traps - Ilahi, Novita Asma; Musyafiq, Afrizal Abdi; Pradana, M. Fakhruriza; Alimudin, Erna; Fadlilah, Ilma; Husna, Kulaiah Syifaul; Nagara, Erliza Septia; Santoso, Agus (MSD Institute, 2025)
Rice is a staple food in Indonesia and globally, but its production is threatened by pests such as the brown planthopper. Conventional pest control methods, including pesticides and traditional techniques, often prove ineffective and have negative environmental impacts. Light traps have been explored as an alternative due to the brown planthopper's phototactic behavior, yet existing designs lack efficiency in capturing pests. This study presents an IoT-based solar-powered pest control system that integrates light as an attractant and an electric trap for effective pest elimination. The system features real-time monitoring of voltage, current, and light intensity using an LCD display, powered by a 35 Wp solar panel and managed through an Arduino Uno microcontroller. Experimental results show that brown planthoppers are most attracted to an LED light with an intensity of 780 lux, operating at 11.5 V and 0.97 A. The system consumes 112.52 Wh, with a full battery charge requiring approximately 6 hours and 7 minutes. These findings highlight the potential of a sustainable, energy-efficient solution for pest control in rice agriculture.